Determination of Residual Solvents in Marbofloxacin by Capillary Gas Chromatography - Liu, Erdong; Li, Zhiwei (Asian Journal of Chemistry, 2012)
The residual solvents in marbofloxacin were determined in this study. Under the optimized conditions, ethyl acetate, dichloro methane, methyl benzene and N,N-dimethyl formamide were detected by capillary gas chromatograph with flame ionization detector. The results showed that the four organic solvents could get a good separation and the internal standard acetonitrile had no effect on the determination. In the test concentration range, the linear relationship was good (r > 99 %) and the RSD values were less than 2 %. The established method is simple, efficient and can be used for the determination of residual solvents in marbofloxacin.